Analisis Dampak Perkembangan Transformasi Bisnis Digital Terhadap Kepastian Hukum Pelaku UMKM - Widadatul Ulya; Hana Afifah; Dyah Awaliyah Mar'ah (Fakultas Hukum, Universitas Warmadewa, 2025)
Government policies related to business activities should not only focus on legal protection but also ensure legal certainty for both business actors and consumers. MSMEs are highly vulnerable to the negative impacts of technology utilization in digital businesses due to their low level of digital literacy. Halal certification through the self-declare mechanism, which should serve as a tool to meet product quality standards as mandated by Law No. 33/2014 and Law No. 6/2023, in practice creates opportunities for fraud and undue levies on MSMEs. On the other hand, Law No. 8/1999 concerning consumer protection has not yet accommodated digital business transactions, resulting in unclear dispute resolution mechanisms. Therefore, research is needed to analyze the impact of digital business development on legal certainty for MSMEs. This empirical juridical research applies a deductive reasoning framework with in-depth analysis and employs both a conceptual approach and a case-based approach. The findings indicate that digital transformation has had a significant impact on the legal aspects of MSMEs. Despite the aim of simplifying processes, the current implementation still faces serious obstacles, particularly those related to digital literacy, system integration, and regulatory ambiguity. A regulatory gap remains, requiring LPH to take an active role in guiding PPH facilitators to comply with policies and avoid unofficial charges. BPJPH is also expected to issue comprehensive policies to strengthen legal certainty.